MODELING OF LIGHT ILLUMINATION FIELD ON MICRO-EXPRESSION FOR FACE RECOGNITION APPLICATION - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
the feature points and thereby degrades the recognition rate. Though past techniques in the same area often requires manual setting of thresholding parameters but in this study the presented technique solves the problem of variation in light illumination by modeling the light field on facial micro expression for improving performance of the face recognition. The performance of the method is compared with the other techniques based on two benchmark datasets namely: CMU PIE & Multi-PIE. Â Â